Microstructure and mechanical properties of as-processed scandium-modified aluminium using selective laser melting. Issue 1 (2016) - Spierings, Adriaan B.; Dawson, Karl; Voegtlin, Mark; Palm, Frank; Uggowitzer, Peter J.
Abstract: Additive manufacturing (AM) offers significant benefits towards optimized lightweight structures for aircraft and space applications. High-strength aluminium alloys are of special interest to reach a maximum mass reduction. The paper presents the development of appropriate selective laser melting (SLM) processing windows for a scandium modified aluminium alloy (Scalmalloy ® ), reaching densities >99%. The mechanical properties of as-processed material are analyzed, pointing out a comparably low anisotropy with regard to the build orientation. A fine-grained microstructure is observed next to regions of coarser, elongated grains. The paper discusses the observed microstructure, and concludes with suggestions for innovative material design for AM.